"Cyberspace ecologism 4.0": Between software softeners of and hardware hardships on the natural environment - Octavian-Dragomir Jora; Adrian-Ioan Damoc; Vlad I. Roșca; Matei-Alexandru Apăvăloaei; Mihaela Iacob (Amfiteatru Economic Journal, 2022)
Planet Earth, with its plethora of natural (im)balances, has a venerable age of 4.54 billion years; the (industrial) imprint placed by the human species on it, considered to be not negligible, counts of just little over two centuries; while the digital/IT&C/virtual existence of man, in what we call cyberspace, is reduced to just a few decades. An amorphous world, hastily assimilated to the Internet, the cyberspace is the sum or, better said, the synergy created by links between computers (and other compatible devices), servers, routers and various items of global IT and telecommunications infrastructures. A sort of fiefdom for tech computing power, but also a field of geo-political-economic power calculus, the cyberspace raises another dilemma: is it the salutary alternative to the bodice of a physical environment subject to depletion/plunder and degradation/pollution of its scarce resources? This article aims to capture, in an original way, how the translation of a great part of the world and social life into cyberspace, especially in the wake of the Fourth Industrial Revolution, relieves the natural environment/climate of Anthropocene pressures (e.g., via optimizations of production processes, favoured by artificial intelligence etc.), or, on the contrary, a less noticeable aspect, how it worsens certain components of it (e.g., via the amplified need for energy or for rare minerals, critical to new technologies etc.). Moreover, the above-mentioned ecological alleviations (labelled as of software nature) and (hardware) aggravations brought by digitalization are duly emphasized and evaluated in the light of the (un)intended consequences occurring at the highly sensitive intersection between markets (private practices) and states (public policies), pointing to the case of the European Union.
Keywords: K32; N54; N74; O13; O14; P00; Q55; Q56; 330; cyberspace; natural environment; technology; ecology; markets; states; economic calculation; public policies